Mnemosine do design: um estudo dos processos funcionais do design a fim de propor uma possível teoria para o design na era digital - Santos, André Luís Reis (2017)
The aim of this thesis is to create a Design Mnemosine to analyze this practice historically, with a focus on the so-called Digital Design. For this, we will use every day experiences to create a reflection on design in contemporary society. The foundations of Peircean, Barthesian and Gestalt semiotics will be the basis for arguing the construction of a possible Design Science in the digital age. The methodology will have as support the bibliographical and documentary survey about the subject, besides field research of qualitative character to investigate the phenomena that involve the professionals of the digital design area. This study will have as objectives: 1) the analysis related to the etymology of the word Design, in addition to other words correlated to the design or elements that compose and accompany the design stages in their social and economic impacts related to Industrial Revolutions; 2) analysis of the characteristics of design in its relationship with society and with technology; 3) study the marks and technical revolutions that interfered in the production and communication of the design function; 4) to study design in the information age, so that the concepts related to the theme and its events help analyze the different ways of producing, doing, thinking and communicating design. With these objectives, it will be possible to understand the technical and projective changes in order to define what Design is in the digital age, tracing its characteristics based on the new form of collaborative and distributed power that characterizes the third Industrial Revolution